Differences weighted composition operators in several variables between some spaces of analytic functions - Al-Ahmadi, Aydah Mohammed Ayed (AIMS mathematics, 2023)
The boundedness and compactness of weighted composition operators have been extensively investigated on various analytic function spaces. In this paper, we study the boundedness and compactness of two several variables differences weighted composition operators on some analytic function spaces.